VNTR polymorphism in the breakpoint region of ABL1 and susceptibility to bladder cancer - Kim, Min-Hye (BMC Med Genomics, 2021)
BACKGROUND: ABL1 is primarily known as a leukemia-related oncogene due to translocation, but about 2.2% of ABL1 mutations have been identified in bladder cancer, and high expression in solid cancer has also been detected. METHODS: Here, we used the NCBI database, UCSC genome browser gateway and Tandem repeat finder program to investigate the structural characterization of the ABL1 breakpoint region and to identify the variable number of tandem repeats (VNTR). To investigate the relationship between ABL1-MS1 and bladder cancer, a case-controlled study was conducted in 207 controls and 197 bladder cancer patients. We also examined the level of transcription of the reporter gene driven by the ABL1 promoter to determine if the VNTR region affects gene expression. RESULTS: In our study, one VNTR was identified in the breakpoint region, the intron 1 region of ABL1, and was named ABL1-MS1. In the control group, only two common alleles (TR13, TR15) were detected, but an additional two rare alleles (TR14, TR16) were detected in bladder cancer. A statistically significant association was identified between the rare ABL1-MS1 allele and bladder cancer risk: P = 0.013. Investigating the level of transcription of the reporter gene driven by the ABL1 promoter, VNTR showed inhibition of ABL1 expression in non-cancer cells 293 T, but not in bladder cancer cells. In addition, ABL1-MS1 was accurately passed on to offspring according to Mendelian inheritance through meiosis. CONCLUSIONS: Therefore, the ABL1-MS1 region can affect ABL1 expression of bladder cancer. This study provides that ABL1-MS1 can be used as a DNA fingerprinting marker. In addition, rare allele detection can predict susceptibility to bladder cancer. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12920-021-00968-1.